Neoplasia within the equine foot: A retrospective case series of four horses. (27th July 2021) - Osborne, C.; Elce, Y. A.; Meehan, L.; Davern, A. J.; Lescun, T. B.
Summary: Background: Trauma to the foot and distal phalanx are common presenting complaints. In contrast, neoplasia of the distal phalanx or hoof region is rarely reported. Within the foot, keratomas are the most frequently reported neoplasm. The gross and radiographic appearance of keratomas is well documented; however, this is less well established for other neoplasms of the hoof capsule. Objective: This paper presents four cases which had clinical and radiographic similarities to keratomas; however, key differences were observed. We aimed to highlight the key differences in imaging findings and clinical progression. Study design: Retrospective multicentre case series. Methods: Cases identified between 2015 and 2019 with pathological diagnoses of neoplasia within the foot at Purdue University Veterinary teaching hospital and Langford Equine Hospital. Clinical records were examined, and physical examination, imaging, surgical and pathological findings are presented. Results: The four cases presented had similarities to keratomas; however, key differences were present. Marked lameness was noted in all three cases with aggressive neoplasia, whereas one case was not lame at presentation but still had a diagnosis of a benign neoplasm. Radiographic examination showed significant lucent areas with poor delineation at the margins and suspected invasion into the distal phalanx. For the two melanomas and the squamous cell carcinoma, deterioration was marked and rapid, ultimately leading to euthanasia. The benign neoplasm was managed successfully for 2 years and lost to follow‐up. Conclusions: Although rare, neoplasms other than keratoma do occur in the foot. Careful interpretation of the imaging findings, consideration of additional imaging such as vascular studies or cross‐sectional imaging, and submission of tissue for biopsy are strongly recommended if there is any suspicion of the lesion being anything other than a keratoma.